On the Development of Expressive Learning Skills - Azizovna, Yuldosheva Saodat (Researchparks Publishing, 2023)
This article focuses on the development of expressive learning skills for students through literary education. Discussion and listening, the historical root of oral performance, the development of expressive art of speech at different periods. Also, in accordance with the National Curriculum, the relevance of the formation of the skills of the artistic word among students, the sense of its attractiveness, knowledge and analysis of the present work of art was noted.